Empirical Analysis Empirical Analysis of the Effect of Information Technology Capability on Performance of Food Processing Firms in Nairobi City County, Kenya: Effect of Information Technology Capability on Performance of Food Processing Firms in Nairobi City County, Kenya - KYENGO, JUSTUS MUTUKU (Archives of Business Research, 2019)
This study sought to investigate the effect of information technology capability on performance. The target population of the study was 102 registered Food Processing Firms. The study used positivism research philosophy and adopted both explanatory and descriptive research designs. Multistage probability sampling technique was used to selecting 31 firms and 155 respondents. The unit of analysis comprised of the food processing firms whereas the unit of observation consisted of the head of functional areas in these firms. Primary data was collected using semi-structured questionnaires. The researcher adopted positivism research philosophy and a mix of explanatory and descriptive research designs. Multistage probability sampling was used to select 155 respondents. Primary data was collected using self-administered structured questionnaires. Descriptive statistics were used to summarize the characteristics of the sample while simple linear regression analysis was used to test the research hypotheses. The study established that information technology capability has a positive effect on performance. Therefore, management should adopt practices such as technological flow, new ideas and new ways of doing things to shore up performance.